Burundi : Request for Modification of Nonconcessional External Debt Limit Under the Extended Credit Facility. (IMF Staff Country Reports; Country Report ;, 2011)
The Burundian government has requested a modification of the zero limit on nonconcessional external debt in the country's arrangement under the Extended Credit Facility (ECF). It has sought to increase the grant element of the financing for the hydroelectric plant. Executive Directors support this request as the benefits of the hydroelectric plant outweigh the additional risk arising from the proposed line of credit. This will help Burundi increase its electricity generation capacity significantly, which has been identified by both donors and businesses as the major constraint to growth.